Causal effects of education on sexual and reproductive health in low and middle-income countries: A systematic review and meta-analysis - Stephanie R. Psaki; Erica K. Chuang; Andrea J. Melnikas; David B. Wilson; Barbara S. Mensch (Elsevier, 2019)
Background: Despite strong theoretical grounding, important gaps in knowledge remain regarding the degree to which there is a causal relationship between education and sexual and reproductive health, as many claims have been made based on associations alone. Understanding the extent to which these relationships are causal is important both to inform investments in education and health, as well as to understand the mechanisms underlying these relationships. Methods: We conducted a systematic review of the evidence for a causal link between education and sexual and reproductive health (SRH) in low and middle-income countries. Education indicators included exposure to formal schooling and learning. SRH outcomes included: age at first sex, age at first marriage, age at first pregnancy/birth, contraceptive use, fertility, and HIV status and other sexually transmitted infections. When possible, we also conducted meta-analyses to estimate mean effects by outcome, and to understand sources of variation between studies. Results: We identified 35 papers that met our inclusion criteria. Although many of the studies report evidence of a causal relationship between education and one or more SRH outcomes, estimated effects are often small in magnitude. Our meta-analyses reveal mostly null mean effects, with the exception of small effects of increased grade attainment on lower fertility and HIV positive status. We also found inconsistent evidence supporting mechanisms linking education and SRH. Conclusions: This review demonstrates that, although investments in schooling may have positive ripple effects for sexual and reproductive health in some circumstances, those effects may not be as large or consistent as expected. Further, our understanding of the circumstances in which schooling is most likely to improve SRH remains somewhat limited. An accurate picture of whether and when improvements in education lead to better health outcomes is essential for the achievement of global development goals. Keywords: Education, Sexual and reproductive health, Systematic review, Meta-analysis, Low and middle-income countries